EFEKTIFITAS TERAPI SENI TERHADAP PENGETAHUAN DAN PERILAKU MENYIKAT GIGI PADA ANAK USIA PRASEKOLAH - Idham Halid; Muliadi Muliadi (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Art Therapy is a process of using art media in therapeutic interventions. This study aims to determine the effectiveness of art therapy on knowledge and practice of brushing teeth in preschool-aged children. This type of quasi-experimental research used a one group pre-post test design involving 32 preschool children aged 4-6 years. Data analysis used the Wilxocon test and the Mann Whitney test. The results showed that the average increase in knowledge was greater in the intervention group (art therapy) of 3.0 compared to the control group (fairy tales) of 1.8. The average increase in behavior was greater in the intervention group (art therapy) of 2.6 compared to the control group (fairy tales) of 2.5. There are significant differences in knowledge and behavior between art therapy and fairy tales, so it can be concluded that art therapy is more effective than fairy tales